Breathing architecture: Integrating nature and cities - Juraev, Sayfiddin; Шадманова, Санобар; Xaitov, Xamza; Yakubjanova, Dilobar; Tulisheva, Gulzina; Tursunov, Mustafo (project baikal, 2026)
The ongoing expansion of metropolitan areas leads to a separation between daily urban activities and the nearby ecosystems, which fragments habitats and lowers the availability of green areas. Based on such challenges, Breathing Architecture proposes a new and cohesive approach to building design which would lead to buildings that actively breathe and would enable the flow of air, light, and energy through porous boundaries instead of rigid shells. The study investigates how urban roofs, facades, and joinery can be synchronized with seasonal rhythms and the local climate. Using concepts from environmental psychology, cultural symbolism, biomimicry, and the research formulates adjustable shading fins, daylight chimneys, adaptive cladding, and other processable design solutions which would functionally reconnect buildings with natural systems.